EU action against discrimination - Activity report 2007-08 (Luxembourg, 2009)
"The report "EU action against discrimination" presents the activities carried out by the European Commission in 2007-08 to fight discrimination on the grounds of racial or ethnic origin, religion or belief, disability, age or sexual orientation as regards to employment and occupation. It describes the policy and partnership aspects, the state of play in the legislation and its implementation at national level including some case law and the various activities conducted to communicate equality."